Bovine alpha-lactalbumin particulates for controlled delivery: Impact of dietary fibers on stability, digestibility, and gastro-intestinal release of capsaicin. (July 2022) - Romano, Alon; Engelberg, Yizhaq; Shani-Levi, Carmit; Lesmes, Uri
Abstract: Consumer demand for functional foods rich in proteins, fiber and bioactives, such as capsaicin (CAP), is constantly growing. This study hypothesized that the electrostatic biopolymer interactions between bovine alpha-lactalbumin (ALA), and the ionic polysaccharides alginate or chitosan (ALG and CHI, respectively) can be harnessed to form fine particulates with improved stability, attenuated susceptibility to digestive proteolysis and controlled release of CAP. Quantitative analysis show that the addition of dietary fiber increases the encapsulation efficiency of CAP up to 10%. Various light scattering techniques affirm that interactions between ALA and the oppositely charged polysaccharides significantly enhances particulates physical and pH stability. Thirty-day shelf-life studies show that the biopolymer complexation helps retain 50% of the entrapped CAP and limits protein aggregation. Semi-dynamic in vitro digestions highlight ALA-ALG particles control ALA digestive proteolysis and CAP release under oral and gastric conditions. Further, LC-MS/MS proteomic analysis of gastric aspirates suggests polysaccharide addition does not have a marked effect on the liberation of anti-inflammatory, ACE- and DPP-IV inhibitory peptides. Moreover, predictive PeptideRank tool helps demonstrate the potential release of possible novel bioactive peptides whose bioactivity requires further investigation. Thus, this study adds another tier to the existing body of evidence supporting protein-polysaccharide complexation as a possible avenue to develop edible delivery systems. Graphical abstract: Image 1 Highlights: Dietary fiber enhances capsaicin encapsulation in alpha-lactalbumin particulates. Alpha-lactalbumin-polyelectrolyte particulates stable for 30 days. Alginate sustains cargo release during in vitro digestion. Bioaccessible peptides are insignificantly affected by polysaccharide addition. Potentially novel bioactive peptides can be generated under gastric digestion.